The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/en17051213
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and Energy in Attaining Sustainable Development: Impact on Energy Consumption, Energy Structure, and Energy Intensity

Henryk Dzwigol,
Aleksy Kwilinski,
Oleksii Lyulyov
et al.

Abstract: The relentless advancement of digital technologies has the potential to significantly reshape the energy landscape as digital technologies become increasingly integrated into diverse sectors of the economy. This study explores the intricate relationship between digitalization and energy in EU countries, focusing on its direct and indirect impacts on energy consumption, structure, and intensity. Furthermore, this study explores the mediating mechanisms that facilitate these changes, including the role of techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Information and communication technologies (ICT) and services have made an important contribution to economic development, resulting in significant improvements in energy efficiency [17]. Henryk Dzwigol et al found a negative correlation between digitization and energy consumption by exploring the intricate relationship between digitization and energy in EU countries [19]. Erdmann and Hilty demonstrated that the digital economy has the potential to reduce traffic flows and energy demand, drive technological efficiency gains and structural change, and reduce greenhouse gas emissions [20].…”
Section: The Digital Economy and Energy Consumptionmentioning
confidence: 99%
“…Information and communication technologies (ICT) and services have made an important contribution to economic development, resulting in significant improvements in energy efficiency [17]. Henryk Dzwigol et al found a negative correlation between digitization and energy consumption by exploring the intricate relationship between digitization and energy in EU countries [19]. Erdmann and Hilty demonstrated that the digital economy has the potential to reduce traffic flows and energy demand, drive technological efficiency gains and structural change, and reduce greenhouse gas emissions [20].…”
Section: The Digital Economy and Energy Consumptionmentioning
confidence: 99%